Efektifitas Pelaksanaan Kurikulum 2013 ditinjau dari Kesiapan Sekolah dan Pengaruhnya terhadap Perkembangan Sekolah - Melkianus Suluh; Dekriati Ate (Postgraduate, University of Mataram, 2019)
Abstract: This study aims to determine: (1) school readiness and response to the 2013 curriculum, (2) the effectiveness of the 2013 curriculum implementation on school development, (3) the supporting and inhibiting factors for the implementation of the 2013 curriculum in physics learning, and (4) Implementation of process standards and curriculum evaluation standards for 2013. This research is a qualitative descriptive study. The research subjects were Physics Teachers, Mathematics Teachers, and Indonesian Teachers. Research data was collected by conducting in-depth interviews. The results of the study show that: 1) the principal and teacher state the readiness for the implementation of the 2013 curriculum. 2) the application of the 2013 curriculum influences the efforts of schools to develop schools through increasing teacher human resources, providing supporting facilities and infrastructure and learning facilities; 3) supporting factors for the implementation of the 2013 curriculum are the availability of adequate teacher resources, the availability of adequate supporting facilities and infrastructure, the support of parents and the government, and the willingness of students. Meanwhile, the inhibiting factors are minimal learning media, limited student books, limited educational staff, readiness and teacher thinking methods that still use old learning patterns; 4) teachers have difficulty implementing scientific approach based learning due to lack of student enthusiasm, minimal learning media, limited laboratory and library facilities and infrastructure, for aspects of assessment teachers experience difficulties with the number of items and forms of assessment.Keywords: 2013 curriculum; School Readiness; School Development